2013
DOI: 10.7763/ijcte.2013.v5.697
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Analysis of Search Engines (Google, Yahoo and Altavista) for Their Search Result

Abstract: Abstract-The web search engines are used to extract query specific information from this massive pool of WWW. A large number of different search engines are available to the user to satisfy their needs. Every search engine uses its own specific algorithm to rank the list of web pages returned by the search engine for the users query, so that the most relevant page appears first in the list. Users think which search engine should be selected for searching corresponding to any query topic for efficient search. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Reward them with a visit." [41] Originally, SERPs contained a list of hyperlinks to pages containing the target keyword; initially, although search results were very similar across the most popular search engines [42], over the years user requirements forced the design of new and more functional forms of presenting results [43]. Search engine algorithms no longer simply respond to queries by analyzing the number of links recommending a particular page: nowadays, they primarily seek to understand the context and intent of the inquirer.…”
Section: Search Engine Results Pagesmentioning
confidence: 99%
“…Reward them with a visit." [41] Originally, SERPs contained a list of hyperlinks to pages containing the target keyword; initially, although search results were very similar across the most popular search engines [42], over the years user requirements forced the design of new and more functional forms of presenting results [43]. Search engine algorithms no longer simply respond to queries by analyzing the number of links recommending a particular page: nowadays, they primarily seek to understand the context and intent of the inquirer.…”
Section: Search Engine Results Pagesmentioning
confidence: 99%
“…With respect to the findings of search engines, Dwivedi, Joshi & Gupta 5 found that search engines (Google, Yahoo! and AltaVista) do not differ significantly whereas Vaughan & Thelwall 6 agreed that search engines (Google, AllTheWeb and AltaVista) found significant differences in their coverage.…”
Section: Discussionmentioning
confidence: 99%
“…Dwivedi, Joshi & Gupta 5 have evaluated three popular search engines, Google, Yahoo, AltaVista, based on three quality parameters which are in depth coverage, ideation and clarity and number of links of related article to query topic. Result shows that these three search engines do not differ significantly in their same query results.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It is a program to automatically download web pages according to rules and it is an important part of the search engine grab system. [1] The information on the Internet is scattered in the hundreds of thousands of web pages, and these pages are stored by millions of servers in every corner of the earth. Users who browse in the web world usually only get information via hyperlinks and they travel through the web pages.…”
Section: Basic Principlementioning
confidence: 99%